A literature review on the Central Chronic Medicine Dispensing and Distribution Programme in South Africa - de Beer, Phillip; Tladi, Keorapetse Mmamphora; Mokoena-de Beer, Andile Glodin (Orapuh Journal, 2025)
The increasing burden of non-communicable diseases (NCDs) in South Africa has placed significant pressure on the healthcare system. As part of the National Health Insurance (NHI) initiative, the need to improve healthcare delivery and medication access arose. In response, the country implemented the Central Chronic Medicines Dispensing and Distribution (CCMDD) program in 2014, establishing external pick-up points for medication collection. This literature review evaluates the implementation of the CCMDD program in South Africa, focusing on patient experiences, implementation challenges, and its impact on the healthcare system. A systematic search of PubMed/MEDLINE, Cochrane Library, African Journals Online, Google Scholar, and CINAHL identified 11 articles published between 2014 and 2024. Braun and Clarke’s thematic method of data analysis revealed four key themes: Patient experience and satisfaction – highlighting positive reception and reduced waiting times. Operational challenges – including communication issues and infrastructure limitations. Program implementation and expansion – showing coverage of 88% of health districts by 2019. Healthcare system impact – demonstrating reduced facility congestion but noting challenges such as missed appointments and medication wastage. The review concludes that while the CCMDD program has shown promise in improving healthcare accessibility and efficiency, ongoing challenges persist, including resource constraints, patient education gaps, and systemic barriers in rural areas. Recommendations for the program’s success include addressing operational barriers, improving infrastructure, enhancing patient education, integrating technology to improve communication systems, ensuring adequate resources for program sustainability, and aligning it with broader health initiatives such as NHI. Further research, adaptive implementation strategies, and the integration of digital health solutions are needed to maximize the program’s benefits.